Actualizing Character Values in Akhlaq Learning: A Study of Moral Formation at Al-Amin Al-Khidary Pesantren, Rajun Pasongsongan, Madura, Indonesia - Ainurrohman, Ainurrohman; Zaini, Fawaid (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2024)
Character education and akhlaq formation constitute foundational dimensions of Islamic moral pedagogy, yet their actualization within pesantren-based learning environments remains insufficiently examined in the existing literature. This study investigates the relationship between character values and akhlaq formation in the learning process at Al-Amin Al-Khidary Pesantren, Rajun Pasongsongan, Madura, Indonesia, with particular attention to how character education values are actualized through the Tarbiyatul Ta'lim Al-Islamiyah (TTI) instructional framework. A qualitative phenomenological approach was employed, with data collected through in-depth interviews, participant observation, and documentation. Data validity was ensured through triangulation, while analysis followed systematic stages of data reduction, data display, and conclusion drawing. The findings reveal that akhlaq learning at Al-Amin Al-Khidary is implemented through two complementary channels. Within the classroom, moral education is delivered through classical texts including Bidayatul Hidayah and At-Tafsir, providing students with a structured foundation in Islamic ethical principles. Beyond the classroom, akhlaq formation is reinforced through structured extracurricular activities encompassing Khutbatul Tholib, pilgrimage, Muhadloroh, Quranic recitation, Sholawat Nabi, and community devotion. Together, these channels create an integrated moral learning environment that extends character formation across all dimensions of santri life. These findings suggest that the TTI framework constitutes a distinctive pesantren-based model of character education with significant implications for Islamic moral pedagogy in Indonesia.